Experimental Investigations of Forced Convection of Nanofluids in Smooth, Horizontal, Round Tubes: A Review - Janusz T. Cieśliński; Przemysław Kozak (Energies, 2023)
A comprehensive review of published works dealing with experimental studies of forced convection heat transfer of nanofluids is presented. The survey is limited to straight, smooth, and round tubes. Moreover, only mono nanofluids exhibiting Newtonian behaviour are considered. Works on experimental research of forced convection in tubes are presented in a chronological order in the first part of the article. In this part, attention was paid to the influence of nanoparticles on the intensification of heat transfer. Information on the tested nanofluids, the measurement technique used, and the measurement range are presented in tabular form. Correlation equations proposed by individual researchers are also presented. In order to explain the controversy regarding the different influences of nanoparticles on the intensity of heat transfer during forced convection of nanofluids, the second part of the paper presents a comparison of the test results obtained by different researchers for the same nanofluid, possibly under the same thermal and flow conditions. Finally, the main conclusions are discussed.